2020
DOI: 10.1055/s-0040-1712172
|View full text |Cite
|
Sign up to set email alerts
|

Does Renal Function Remain Stable after Puberty in Children who underwent Ureteral Reimplantation due to Ureterovesical Junction Obstruction?

Abstract: Introduction Ureteric reimplantation due to ureterovesical junction (UVJ) obstruction enjoys high success in the short term. However, renal function after reimplantation must accommodate the numerous changes in the pediatric urinary tract that occur along with child development that may theoretically cause an occult loss of renal function. The purpose of this study was to evaluate whether improved renal function after ureter reimplantation for antenatal diagnosed UVJ obstruction remains stable after puberty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Research showed that the Yang-Monti Ileal ureter is durable and effective in enhancing kidney function with few complications in kidney function loss and SK, as evidenced by long-term renal function outcomes ( 14 ). The previous studies confirmed that renal function generally remained stable after ureter reimplantation surgeries ( 15 , 16 ). Another study assessed the long-term functional outcomes of 62 SK patients after pyeloplasty, revealing that pyeloplasty preserved renal function in 90.4% of the SK patients ( 8 ).…”
Section: Discussionsupporting
confidence: 66%
“…Research showed that the Yang-Monti Ileal ureter is durable and effective in enhancing kidney function with few complications in kidney function loss and SK, as evidenced by long-term renal function outcomes ( 14 ). The previous studies confirmed that renal function generally remained stable after ureter reimplantation surgeries ( 15 , 16 ). Another study assessed the long-term functional outcomes of 62 SK patients after pyeloplasty, revealing that pyeloplasty preserved renal function in 90.4% of the SK patients ( 8 ).…”
Section: Discussionsupporting
confidence: 66%
“…This examination cannot be performed in our center because a nuclear medicine department has not been set yet. Based on CT and IVU examinations, the renal cortex thickness of the upper kidney and the secretion of contrast agent were observed to evaluate whether there was any retention value ( 7 ). In this study, preoperative imaging examination showed that it was valuable to preserve the upper kidney in all the children.…”
Section: Discussionmentioning
confidence: 99%
“…We previously published our protocol for performing a DMSA scan [5]. The Technetium 99m DMSA renal scans were undertaken to assess relative renal function (RRF) using background corrected regions of interest of each kidney in the posterior view and calculating the resultant percentage uptake.…”
Section: Methodsmentioning
confidence: 99%